Collaboration Management in the Center of Excellence Program at State Vocational High School 56 Jakarta - Valentine, Stephany; Listyasari, Winda Dewi; Susanto, Teguh Trianung Djoko (PT. BATARI EDU CALYA, 2025)
This study examines collaborative management in implementing the Center of Excellence Vocational High School (SMK PK) Program in the Mechatronics Engineering Expertise Program at SMKN 56 Jakarta. Using a qualitative approach, data were collected through observations, documentation, and in-depth interviews from 2023 to 2024. The findings were analyzed using the P.O.A.C. (Planning, Organizing, Actuating, Controlling) managerial framework. The planning stage reflected systematic, needs-based efforts involving all school stakeholders. Organizing involved internal and external collaboration with partners such as PT. Unggul Semesta and PT. Panca Anugerah Sakti in budgeting and curriculum development. In 2023, all main activities were implemented, while in 2024, progress continued despite one pending activity. The controlling stage emphasized transparency, accountability, and sustainability through industry-based teacher certification. The results indicate that the collaborative management model at SMKN 56 Jakarta has been implemented effectively and offers potential for long-term sustainability.